Luminescence Characteristics of LiCaAlF\(_6\):Eu TLD Phosphor - Abhishek; Sahare, Aditya; Sahare, Siddharth; Singh, Manveer; Sahare, P.D. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
The material LiCaAlF\({}_{6}\):Eu (0.1 mol%) in microcrystalline form was prepared through water solution coprecipitation method followed by melting it at around 900 \({}^°\)C in a graphite crucible. The ingot was crushed and sieved through standard sieves to obtain powder approximate in the range 100-125 \(μ\)m. The material was annealed at around 200-800 \({}^°\)C. The material was characterized by XRD. The materials were irradiated to different doses of \(γ\)-rays using \({}^{60}\)Co radioactive source and thermoluminescence (TL) glow curves were recorded. The powder material was found to be at least 10 times more sensitive than CaSO\({}_{4}\):Dy commercially available TLD pellets. However, as the dosimetry peak is at around 180 \({}^°\)C, there is fading around 20%. Considering these facts, the material could be considered as a highly sensitive and suitable TLD phosphor.